Peningkatan Kemandirian Ekonomi Pesantren Berbasis Agribisnis di Lingkungan Pondok Pesantren Raudhatus Salaam Berbah – Sleman: Improving the Economic Independence of Pesantren based on Agribusiness in the Raudhatus Salaam Islamic Boarding School Environment Berbah – Sleman - Nasrullah Nasrullah; Gunawan Budiyanto; Gatot Supangkat Samidjo; Fawaz Muhammad Ihsan; Kevin Syahru A'zham; Indah Marwani; Martini Martini (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Raudhatus Salaam Islamic Boarding School Berbah Sleman Regency's operating costs are still heavily reliant on student fees and donations from donors, but it has three vacant waqf land locations that have yet to be developed to support pesantren's economic independence. The goal of this Community Partnership Program is to initiate efforts to increase the economic independence of pesantren through agribusiness-based activities by optimizing the existing resources. The data collection method used in this activity is observation and focus group discussion, while the method of service implementation is through counseling, land clearing, planting, and post-planting maintenance. The study's data were analyzed quantitatively and qualitatively. This program has been successful in increasing the empowerment of partners in terms of knowledge and skills, with the goal of increasing the economic independence of the partners' pesantren by converting one of the existing lands into a banana plantation.